The Effect of Dhikr Therapy on Increasing The Meaningfulness of Life in Students at The Satu Amal Indonesia Foundation - Rayuni Larasaty.AZ; Putri Wulandari; Muhammad Iqbal Alhadii (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This study aims to determine the effect of dhikr therapy on increasing the meaningfulness of life experienced by students who are members of the Satu Amal Indonesia foundation. This study uses a one-group pretest-posttest design method because it can compare conditions before and after being given treatment. With various treatments carried out for 7 days or one week on WhatsApp Group. This study presents the results of the effectiveness test of dhikr therapy on the meaningfulness of life using the "Paired Sample t-Test" method. The results in this study involved 20 participants who showed a significant increase in the meaningfulness of life after undergoing dhikr therapy. Before therapy, participants had a moderate level of meaning in life, while after treatment or therapy, the level of meaning in life increased to high. A strong positive correlation between pretest and posttest indicates a significant relationship. Statistical tests showed a significant difference between pretest and posttest scores, with a p value of less than 0.001, confirming that dhikr therapy had a significant effect on participants' meaningfulness of life. These results illustrate that dhikr therapy can markedly improve an individual's meaningfulness of life.